Finding meaning in the text : translation technique and theology in the Septuagint of Amos - Glenny, W. Edward. (Vetus Testamentum, Supplements, 2009)
This book offers a thorough analysis of the translation technique and theology of LXX-Amos, which will be valuable for those studying LXX-Amos and for those doing textual criticism in the Hebrew text of Amos. It analyzes the literalness of the translation, the rendering of difficult and unknown words, and the rendering of visually ambiguous phenomena, like homonyms, homographs, and word divisions. The evidence suggests the translator worked from a text very similar to the MT. He reveals his biases as he struggles with the difficult and obscure sections of his source text. He exhibits an anti-Syrian and anti-Samaritan bias as well as interest in Gentiles, eschatology, and messianism.